STUDENTS’ PERCEPTION ABOUT THE CLINICO-ANATOMICAL CONFERENCES AS A TEACHING METHODOLOGY - Saeed, Kanwal; Baptist, Marina; Mukhtar, Fatima (Journal of Ayub Medical College Abbottabad, 2015)
Background: Anatomy has always been considered as an essential basis for clinical sciences. In recent decades there has been an increased trend towards incorporation of clinical problems in the teaching of anatomy. To promote clinical knowledge clinico-anatomical conferences have been conducted in our department for the last five years. This study has been undertaken to determine perception of medical students regarding these conferences and to formulate recommendations for their improvement based on feedback obtained from students. Method: A cross-sectional study was conducted from December 2013 to January 2014 at the Lahore Medical & Dental College (LMDC), Lahore. A sample of 200 students of first and second year MBBS classes was selected for the study through convenience sampling technique. A 5-point Likert scale ranging from 1 (strongly agree) to 5 (strongly disagree) was used to determine students’ perception about clinic-anatomical conferences, using a self-administered questionnaire. Data was analysed using SPSS-19.0. Results: Out of total 144 (72%) students were of the opinion that clinico-anatomical conferences were a good source of clinical knowledge, 126 (63%) opined that these conferences promoted understanding rather than memorization, 122 (61%) found them interesting, and 15 (30%) found improvement in their grades in the subject of anatomy after attending the conferences. Conclusion: The clinico-anatomical conferences were found interesting and reported to be a good source of clinical knowledge. It is recommended that these conferences should be conducted frequently, made interactive and patients should be presented as case studies during the conferences Keywords: Clinico-anatomical conference, teaching methodology, anatomy, students’ perceptions.